The Implementation of English for Tour Guide Program in Trenggalek - Dwi Wahyuningtyas; Ria Arista Asih; Alyaa' Chiquita Fairuzara A. R.; Fredik Yunior Heuvelman (Future Science, 2022)
East Java has some famous and potential tourist places, one of which is in Trenggalek. Trenggalek is rich in natural resources such as beaches, mountains, and forests to name a few. Therefore, Trenggalek claimed to have big potential in East Java tourism in 2022. In 2021, the government of Trenggalek already set the target to build and develop 100 tourist villages by 2024. In 2022, 35 tourist villages have been built all around Trenggalek. Skilled tour guides are strongly required to promote Trenggalek as a promising and potential tourism destination in East Java. These tour guides have to master and comprehend English as an international language. Tour guides who can use and speak English well can gain more foreign tourists and make Trenggalek not only famous in East Java and Indonesia but also in wider scopes. Therefore, a PIKAT team of UPN “Veteran” Jawa Timur held a community service program, “English for Tour Guide” in Dongko, Trenggalek, East Java. The team has run this program since July; split into two sessions; offline and online session. The offline session was held in July, at Taman Watu Kandang, Pandean, Dongko, and Trenggalek, and continued with an online session in August via Zoom. Both the offline and online programs were successfully held. The participants joined the program enthusiastically and actively. This community service was supported by the Department of Tourism and Culture of Trenggalek. In the future, the team expects to widen the scope of this community service program.